US dominance of research on political communication: a meta-view - Boulianne, Shelley (My University, 2019)
The United States is the focal point of research on political communication. The dominance of the US scholarship is not an outcome of the efforts of a single peer reviewer, but rather an outcome of a larger system of knowledge production. Rojas and Valenzuela’s (2019) essay points out two issues related to cross-national research in political communication: how the US is treated as the “context-less” norm and how American scholarship shapes expectations for other areas of the world. Adding to this argument, I provide data about citation patterns in subfields within political communication as well as provide a summary of recent meta-analysis studies in political communication. These data affirm the US dominance in political communication scholarship.
Keywords: political communication; United States; cross-national; meta-analysis; publication bias; citation patterns